The glass palace : illusions of freedom and democracy in Qatar - Beydoun, Nasser M. (Algora Pub., 2012)
Is Qatar actually a suitable ally or a legitimate partner for the United States? Under Qatari labor law, foreign workers are actually owned, for all practical purposes, by their Qatari sponsors in a system akin to slavery. This book chronicles the experience of an American executive working in Qatar and delves into Qatar?'s feudal work-sponsorship system, showing that an economic great leap forward is not necessarily accompanied by modernization, despite superficial emblems; that prosperity and democracy need not go hand in hand; and that being a US ally may be totally unrelated to any notion.